What is Wrong with Nicostratus? (Ar. Vesp. 82–83) - Zeltchenko, Vsevolod (Hyperboreus, 2023)
In Vesp. 71 ﬀ. two slaves invite the audience to guess what dangerous disease, beginning with φιλο-, their master’s father is ill with. The named Athenians make their assumptions, each of which somehow compromises the person who oﬀers it: ﬁrst φιλόκυβος, then φιλοπότης, and ﬁnally a certain Nicostratus shouts out the strange φιλοθύτης ἢ φιλόξενος. The scholia, followed by old commentators, understand φιλοθύτης as δεισιδαίμων (which has no parallel); modern opinio communis suggests that φιλοθύτης ἢ φιλόξενος means an over-hospitable amphitryon, i.e. a careless spender or a boastful aristocrat: Nicostratus attributes these qualities to Philocleon because he himself is one. The present paper stresses that φιλοθύτης and φιλόξενος are unconditional virtues, both private and public, and it is impossible to give them any pejorative meaning. Aristophanes’ joke is that only Nicostratus, and no one else, paradoxically considers spending on sacriﬁces and guests to be vices, and that all φιλοθύται and φιλόξενοι are dangerous madmen who must be guarded by their household. In other words, Nicostratus, whoever he was, is ridiculed by Aristophanes as a miser.